Research progress on the structure of hydration films at solid–liquid interfaces - Na ZHANG; Jue KOU; Chunbao SUN (工程科学学报)
Solid–liquid interfaces are pervasive across the material world, playing a crucial role in various fields such as mineral flotation, oil mining and processing, and soil improvement. At these interfaces, the hydration film, a nanostructure, significantly influences their properties. The structure and thickness of the hydrated film are affected by the properties of the solid surface and the solution. This review takes mica and calcite as examples and summarizes advances in understanding the structure of hydration films at solid–liquid interfaces through X-ray reflectivity (XR) and atomic force microscopy (AFM). It discusses the structures of hydration films on different mineral surfaces. It discusses how metal cations in solution, as well as ion dissociation, affect the mineral surface on these structures. The mica surface participates in ion exchange with H3O+ or other cations in the solution, resulting in a hydration film consisting of an adsorbed layer followed by the first and second hydration layers. Ca2+ and \begin{document}${CO}_3^{2-} $\end{document} dissociate and interact with the hydration film, creating a checkerboard-like pattern. The hydration film encompasses four layers, with Ca2+ and \begin{document}${CO}_3^{2-} $\end{document} sites alternating within. The thickness of the hydration film varies with ion concentration and type in the solution. For example, as the K+ concentration increases, the thickness of the hydration film on the mica surface increases. However, when K+ is replaced by Cs+ in the solution, the thickness of the hydration film on the mica surface reduces or even disrupts this film. The hydration film structures obtained by XR and AFM are also compared. XR measurements provide the electron density distribution on the crystal surface, allowing for analysis of the hydration film’s structure. By contrast, AFM measures the force–distance curve between the probe and the water on the sample surface, along with corresponding imaging. Both XR and AFM provide information on the thickness and structure of the hydration film on the mineral surface. However, the boundary between the mineral surface’s hydration film and bulk water is not defined owing to the dynamic nature of hydration films, leading to variations in measured thickness across different instruments, generally in the range of several nanometers. The objective of this review is to deepen understanding of the hydration structure at the solid–liquid interface, promoting further research into the dynamic behavior of hydration films.